P25 and Rutile Titania in Photocatalytic Degradation of Phenol and Methylene Blue (JSSE - Journal of Science & Sustainable Engineering, 2024)
Phenolic compounds, dyes, and their derivatives are prevalent organic pollutants in surface waters due to industrial activities, effluent discharge, and agricultural runoff. In this context, this study aimed to evaluate the photocatalytic activity of commercial P25 TiO2 (TiO2-P25) and rutile TiO2 (TiO2-R) solids for the degrading phenol and methylene blue dye in a batch reactor under UV-C irradiation at 256 nm. X-ray diffraction data confirm the predominant presence of the anatase phase in TiO2-P25 and the rutile phase in TiO2-R. Significant difference in crystallite size and specific area (SBET) between the samples were linked to their commercial synthesis method. The results demonstrated that TiO2-P25 exhibited higher photocatalytic activity than TiO2-R due to differences in band gap. The use of a 15W lamp further enhanced this efficiency. For phenol degradation, TiO2-P25 obtained 57% conversion at 9W and an 11% increase in the initial concentration at 15W, while TiO2-R showed lower efficiency. In photolysis, minimal conversion was observed. Total organic carbon (TOC) data suggest that photocatalysis generates organic metabolites rather than achieving complete mineralization, leading to the accumulation of intermediates in the effluent, particularly with the 15W lamp.